2019
DOI: 10.1111/jocd.13124
|View full text |Cite|
|
Sign up to set email alerts
|

Serum YKL40: A novel potential link between inflammation and dyslipidemia in acne vulgaris

Abstract: Background Acne vulgaris (AV) is an inflammatory skin disorder that may be associated with metabolic disorders. The relation between lipid profile in acne is not widely investigated. Chitinase‐3‐like protein 1 (YKL‐40) has been found to be implicated in different inflammatory conditions. Aims We aimed at investigating the role YKL‐40 in acne pathogenesis and associated dyslipidemia in acne patients. Patients/Methods This study included 50 acne vulgaris patients and 30 matched control subjects. Serum YKL‐40 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Patients with acne vulgaris in this study exhibited significantly higher serum levels of YKL-40 than healthy control volunteers. This outcome was consistent with the findings of Khaled et al 4 and Ebrahim et al, 12 who found that acne vulgaris patients had higher serum levels of YKL-40 than healthy control individuals. The median YKL40 level significantly (P value 0.001) decreased before and after receiving isotretinoin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patients with acne vulgaris in this study exhibited significantly higher serum levels of YKL-40 than healthy control volunteers. This outcome was consistent with the findings of Khaled et al 4 and Ebrahim et al, 12 who found that acne vulgaris patients had higher serum levels of YKL-40 than healthy control individuals. The median YKL40 level significantly (P value 0.001) decreased before and after receiving isotretinoin.…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis displayed that there is insignificant difference between serum level of YKL-40 and disease severity (P value = 0.105) with lower level of YKL40 among moderate AV cases (48.5 (21.5-103.5 ng/mL)) compared with severe AV cases (63 (18-181 ng/mL)). Our results were aligned with Ebrahim et al, 12 that noted that the higher level of YKL-40 may only reflect the level of systemic inflammation in AV patients, and its concentration does not relate with the severity of skin changes in the study.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The elevated YKL-40 serum concentration was also reported in patients with acne vulgaris ( 33 ). In the quoted study, no association was found between the YKL-40 level and the severity of the disease, but a positive correlation was observed between the concentration of the discussed factor and total cholesterol, triglycerides, and low-density lipoprotein (LDL) and negative correlation with high-density lipoprotein (HDL), which may indicate other mechanisms leading to the increase in YKL-40 level.…”
Section: Discussionmentioning
confidence: 65%
“…In the article by Ebrahim et al, 1 Dr. Fathi's surname had inadvertently been misspelled in the original publication. We apologize for the error.…”
mentioning
confidence: 99%